"'It will crush you like a bug': Maternal incarceration, secondary prisonization, and children's visitation". (July 2018) - Aiello, Brittnie L; McCorkel, Jill A
Over the last three decades, the number of children experiencing the incarceration of one or both parents has grown dramatically. Although the children of prisoners are not under legal sanction, they are nonetheless indirectly subject to the coercive apparatus of the state by virtue of their parent's status and they are directly subject to this apparatus during their visits to correctional facilities. In this ethnographic study of a mother–child visitation program in jail, we examine secondary prisonization among children of incarcerated mothers. Previous research on secondary prisonization has focused primarily on adults, finding that contact with the prison system alters their conception self, body, moral statuses, emotions, and relationships. Our ethnographic data demonstrate that the implications of this for children are considerable. Here, we analyze secondary prisonization as it impacts children across two domains: discipline of the body and regulation of emotion.